Innovative moments and change in Career Construction Counseling - Cardoso, Paulo (2014)
This article presents an exploratory study of the process of change during Career Construction Counseling (CCC). The Innovative Moments Coding System (IMCS) and the Return to the Problem Coding System (RPCS) were used to an intensive analysis of a career counseling case — the case of Michael. Both systems are grounded in a narrative conception of the self which suggests that narrative change results from the elaboration and development of narrative exceptions to a client's core problematic self-narrative. The IMCS identifies and tracks the occurrence of five different types of narrative change and the RPCS tracks the ambivalence present in the clients discourse throughout the therapeutic process. This is the first attempt to use these methods with a career counseling case. The results suggest that the narrative elaboration progresses from the first to the third session. We discuss these results, emphasizing the process of change in career counseling with clients in which maladaptive repetition underlies career decision-making difficulties.